2002
DOI: 10.1051/lait:2002016
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning-in-place in the dairy industry: criteria for reuse of caustic (NaOH) solutions

Abstract: -Cleaning-in-place NaOH solutions from a milk standardisation dairy plant are reused for several days before being discharged to the purification station. During reuse the surface tension of the industrial cleaning solutions was reduced from~70 mJ . m -2 for newly prepared NaOH down tõ 30 mJ . m -2 during the week. The decrease was rapid during the first few reuse cycles and stabilised thereafter, while the polluting load and suspended solids increased inversely. The cleaning efficiency test consisted of an ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
1
38
1
Order By: Relevance
“…Recent work Merin, Ge´san-Guiziou, Boyaval, & Daufin, 2002) has shown that re-use of caustic solutions induces a progressive increase in concentration of suspended solids (SS) and of chemical oxygen demand, both total (COD t ) and soluble (COD s ). This causes a decrease in surface tension (g) of the cleaning solutions, to levels around 30 mJ m À2 in the course of the cleaning cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work Merin, Ge´san-Guiziou, Boyaval, & Daufin, 2002) has shown that re-use of caustic solutions induces a progressive increase in concentration of suspended solids (SS) and of chemical oxygen demand, both total (COD t ) and soluble (COD s ). This causes a decrease in surface tension (g) of the cleaning solutions, to levels around 30 mJ m À2 in the course of the cleaning cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The pH is acidic, values measured in the different points (Table 2) are different from those found in Table 1; these variations are linked to an overdose of acid-base cleaning products [10]. This magnitude of the pH shift is detrimental to the environment [11].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of works describing how to recover contaminated cleaning solutions by membranes (Choe et al, 2005;Fernández et al, 2010;Gésan-Guiziou et al, 2002Merin et al, 2002;Räsänen et al, 2002). Dresch et al (2001) pointed out the NF technology as a promising technique compared to decantation, centrifugation and microfiltration (0.1µm cut-off) for the regeneration of waste NaOH solutions from an industrial CIP system.…”
Section: Recovery Of Cleaning-in-place Solutionsmentioning
confidence: 99%